Stress properties of Greek compounds: Psycholinguistic considerations. (March 2015) - Tsiamas, Athanasios; Jarema, Gonia; Kehayia, Eva; Chilingaryan, Gevorg
Abstract: Theoretical accounts of Greek compounds argue for a close relation between their stress properties and their underlying structure. Compounds that preserve and receive stress at the same position as their second constituent are analyzed as stem-word constructions, while those that receive antepenultimate stress are viewed as belonging to the stem-stem category. Using an auditory lexical decision task, we examine the effect of stress change on the processing of compounds in the light of existing theoretical linguistic accounts. Although our experimental results do not reach statistical significance, we believe that they are informative of the cognitive status and role of stress in compound processing. Finally, they relate to existing theories of compounding in Greek and reflect the complex interaction of the psycholinguistic effects of stress and the structural properties of these constructions.